Accounting Processes in Palestine During the Tenth-Eighth Centuries B.C.E - Cornelius, Lynne (Journal for Semitics, 2017)
This article aims at determining what, if any, accounting processes were employed during the first millennium B.C.E. in Palestine, focusing on the tenth to the eighth centuries B.C.E., and whether they conform to the components of the definition of accounting, which comprise: (a) to select relevant information; (b) to perform calculations; (c) to record the information; and (d) to give account. The evidence from Arad, Samaria and Tell QasÃ®le demonstrates that the adopted processes can be regarded as accounting processes since they conform to at least three of the four components of the definition of accounting.